Designing Assessment Instruments for Mild Intellectual Disability Students on Gardening Product Marketing - Ratnawulan, Teti; Septiana, Fajar Indra; Qohar, Hendri Abdul; Novianti, Ranti; Nurdiani, Ani (Journal of ICSAR, 2024)
The study focuses on understanding the challenges, capabilities, and requirements of students with mild intellectual disabilities in marketing skills related to vegetable gardening. It aims to create a suitable learning assessment tool for these students. The researcher observed that teachers lacked a specific assessment instrument for evaluating the marketing of garden products. Consequently, a teacher improvised a self-made assessment. The research methodology employed a descriptive approach within a qualitative framework. Data collection methods included observation, interviews, documentation analysis, Focus Group Discussions (FGDs), and validation. Validation involved multiple stakeholders: a class teacher, a vice head of curriculum, a vocational teacher, and two students with mild intellectual disabilities. The assessment instrument, tailored for mild intellectual disability students, focused on three main aspects: self-development, language and mathematics abilities, and marketing theories. Two validators validated this instrument. The study anticipates several implications: students may enhance their skills and insights, teachers can improve teaching quality, school principals can better address learning needs, and parents gain insights into their children's interests and talents. The research addresses the dearth of appropriate assessment tools for marketing gardening products to students with mild intellectual disability. Its findings are poised to benefit various stakeholders, including students, teachers, school administrators, and parents, by fostering skill development, enhancing teaching quality, and facilitating a better understanding of students' needs and abilities.